Devaluating the Aliran Politics: Views from the third Congress of the PPP - Saiful Mujani (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
This article suggests the political dynamics that occur at the time of the conference the Partai Persatuan Pembangunan (PPP), which was held on 29 August to 2 September 1994.Many opinions that say that the congress of the United Development Party (PPP) that has its own strategic significance because the results will determine the 1997 election and then General Session, 1998. At this General Assembly will take place according to many in the national succession, including the change of state leaders, the president Republic of Indonesia. So many groups concerned with this third congress PPP: who is leading the party's control she would participate in such an important time of succession.DOI: 10.15408/sdi.v1i3.853